2008
DOI: 10.1016/j.thromres.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and consequences of portal vein and systemic thromboses in hepatocellular carcinoma

Abstract: Introduction-Hemostatic activation may be important for tumor biology. Hepatocellular carcinoma (HCC) is commonly associated with portal vein thrombosis (PVT). Little is known about factors predictive for PVT in patients with HCC or its correlation with systemic venous thromboembolism (VTE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 51 publications
(53 reference statements)
6
81
1
2
Order By: Relevance
“…Subsequent diagnostic contrast-enhanced CT was able to locate the tracer accumulation in the portal vein, indicating tumor invasion as a common finding in patients with advanced HCC (22). In these 3 patients, the exclusion of extrahepatic MAA deposition was important to enable radioembolization with 90 Y microspheres.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent diagnostic contrast-enhanced CT was able to locate the tracer accumulation in the portal vein, indicating tumor invasion as a common finding in patients with advanced HCC (22). In these 3 patients, the exclusion of extrahepatic MAA deposition was important to enable radioembolization with 90 Y microspheres.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced stage, higher CTP class, major vessel involvement, low serum albumin and high AFP levels are predictive of PV obstruction in patients with HCC. 180 In a study on thrombophilic genetic factors in 94 patients with HCC with & without PV obstruction, the Odds Ratio was 3.85 for MTHFR C6777TT with HCC versus healthy controls. Prothrombin gene G20210A mutation was also more frequent among HCC patients mainly with PV obstruction thereby concluding that all cirrhotics should be looked for thrombophilic genetic factors to individualize patients at risk for PV obstruction in HCC.…”
Section: Portal Vein Obstruction In Hccmentioning
confidence: 99%
“…[5] It was also observed that patients with PVT also suffered from a higher incidence of systemic VTE (as in this patient) suggesting an underlying common haemostatic activation that predisposes to both local and systemic thrombotic events in patients with HCC. Expression of tissue factor by HCC has been implicated for both the local and systemic hypercoagulable state of HCC.…”
Section: Discussionmentioning
confidence: 60%